Radiation Dose Assessment Using 3D Quantitative Spect/Ct Imaging In Low Risk Differentiated Thyroid Cancer Patients - A Halim, Fatin Nadhirah (2023)
The prevalence of thyroid cancer continues to increase widely. Surgery, radioiodine therapy, chemotherapy, thyroid hormone therapy, and targeted therapy are all applicable options for the treatment of thyroid cancer, either alone or in combination. This study only include patients with low-risk thyroid cancer of a specifically differentiated thyroid cancer type who have undergone total thyroidectomy (TT). These patients were referred to the Nuclear Medicine Department at Penang Hospital for radioactive iodine ablation therapy and received 2960 MBq to 3700 MBq of fixed administration activity. The utilisation of the fixed activity practice poses a challenge in assessing the extent to which the radioiodine activity would result in a lethal dose to normal organs or a tolerable dose that can be assimilated by the body. Based on the Medical Internal Radiation Dosimetry principle, the study's aim is to determine the individual radiation dose to the thyroid remnant and selected organs such as the liver, spleen, kidney, lung, and bone marrow. A quantitative three-dimensional (3D) technique was used to acquire the patient specific density map (from CT image) and activity map (from SPECT image) in conjunction with blood dosimetry utilising Single Positron Emission Computed Tomography in combination with Computed Tomography (SPECT/CT) imaging. Blood dosimetry was estimated using OLINDA, IDAC, and EANM technique.